Job insecurity and organizational citizenship behavior: The role of affective commitment - Debora Eflina Purba; Fahri Muhammad (HUMANITAS: Indonesian Psychological Journal, 2020)
Previous research showed inconsistent findings in the relationship between job insecurity and OCB, indicating an underlying mechanism to occur between the variables. This study aimed to examine affective commitment as a mediator in the relationship between job insecurity and organizational citizenship behavior (OCB). Drawing on organizational identification theory, we took on the perspective of organizational concern motive and suggested affective commitment to mediate the job insecurity and OCB relationship. The study employs a correlational design with an accidental sampling technique. Participants of the study were employees of private and state-owned companies in Indonesia (N = 217). Data were analyzed on Hayes’s PROCESS macro on SPSS statistic software. Results show a significantly negative relationship between job insecurity and OCB, significantly negative relationship between job insecurity and affective commitment relationship, and a significantly positive relationship between affective commitment and OCB. Furthermore, affective commitment is found to mediate the relationship between job insecurity and OCB, confirming the organizational concern motive of OCB as a consequence of job insecurity. The study implies that organizations should eliminate job insecurity if possible, or design interventions to develop employee’s oneness with the organization.